The Effectiveness of Project-Based Learning in Developing Sustainability Awareness and Critical Skills in High School - Ni Gusti Ayu Putu Eka Sri Wahyuni; Emy Nuriyani; Ebi Rahmat Indar Maya; Nurasyah Dewi Napitupulu; I Komang Werdhiana (Postgraduate, University of Mataram, 2026)
The integration of sustainability principles and critical thinking into science learning remains limited, particularly in vocational high schools, despite their importance for achieving Education for Sustainable Development (ESD). This study aimed to examine the effectiveness of Project-Based Learning (PJBL) in improving students' sustainability awareness and critical thinking skills. A quasi-experimental method with a pretest–posttest control group design was employed involving 64 eleventh-grade students at SMK Negeri 1 Parigi, consisting of 32 students in the experimental group and 32 students in the control group. The experimental group received Project-Based Learning, whereas the control group was taught using conventional instruction. Data were collected using a sustainability awareness questionnaire and a critical thinking skills test. The data were analyzed through normality and homogeneity tests, independent samples t-test, and N-Gain analysis. The results revealed significant differences between the experimental and control groups (p < 0.05). Students taught using Project-Based Learning achieved higher learning gains in sustainability awareness (N-Gain = 0.68, medium category) and critical thinking skills (N-Gain = 0.73, high category) compared with those receiving conventional learning. The findings indicate that authentic environmental projects, collaborative learning, and reflective activities effectively enhance students' sustainability awareness while simultaneously fostering higher-order thinking skills. Therefore, Project-Based Learning is recommended as an effective instructional approach for integrating sustainability values and developing twenty-first-century competencies in vocational science education.